The measurement characteristics of upper-quarter posture in female adolescents : a comparison between competitive freestyle swimmers and non-swimmers - Camacho, Tanya Chantelle de Sousa (University of Pretoria, 2026)
Dissertation (MSc)--University of Pretoria, 2018.